Pure white cell aplasia induced by mesalazine in a patient with ulcerative colitis. (May 2013) - Frattini, Francesco; Crestani, Silvia; Vescovi, Pier Paolo; Franchini, Massimo
Abstract : Objectives and importance: Mesalazine is a widely used and generally safe drug for the treatment of chronic inflammatory bowel diseases. Neutropenia rarely complicates this treatment and very few cases have been reported in the literature. Clinical presentation: We report here the case of a patient with ulcerative colitis who developed a severe febrile neutropenia during treatment with mesalazine. Intervention: Drug withdrawal and treatment with granulocyte colony-stimulating factor resulted in a complete and durable remission of cytopenia. Conclusion headings: We recommend periodic blood count monitoring in all patients undergoing treatment with mesalazine.